PENGARUH ETIKA KERJA DAN LOYALITAS TERHADAP PRODUKTIVTAS KERJA KARYAWAN PADA PT. BANK SUMSEL BABEL CABANG JAKABARING PALEMBANG - Lusmasari, Ida Ayu; Mafra, Nisa ’Ulul; Darmawati, Tri (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of work ethics and loyalty partially and simultaneously on the work productivity of employees at PT. Bank Sumsel Babel Jakabaring Palembang Branch. The population in this study are all employees of PT. Bank Sumsel Babel Jakabaring Palembang Branch has as many as 44 employees. The data collection technique is a survey by spreading the questionnaires. The instrument testing technique is validity and reliability testing and the analytical method used is multiple linear regression analysis with SPSS software version 22. The partial test (t) results of the work ethic variable partially have no significant effect on work productivity at PT. Bank Sumsel Babel Jakabaring Palembang Branch. The better the work ethic of employees does not necessarily increase the productivity of good work. The results of the loyalty variable's partial test partially have a significant influence on work productivity at PT. Bank Sumsel Babel Jakabaring Palembang Branch. The results of the F-test showed that the variables of work ethics and loyalty simultaneously had a significant effect on work productivity at PT. Bank Sumsel Babel Jakabaring Palembang Branch. Keywords: Work-ethic; Loyalty; Work productivity